The sleeping giant of Goll - Abbott, Tony, 1952- (Abbott, Tony, 1952- Secrets of Droon, 2000)
Lord Sparr has found a new weapon to use against the city of Droon. He's woken up a mean old giant that will now obey his every command! It's a good thing Eric, Julie, and Neal are around to help their friends try to stop Lord Sparr. It's a giant job, but somebody's got to do it!